Global and Regional Development of the Human Cerebral Cortex: Molecular Architecture and Occupational Aptitudes. (20th March 2020) - Shin, Jean; Ma, Shaojie; Hofer, Edith; Patel, Yash; Vosberg, Daniel E; Tilley, Steven; Roshchupkin, Gennady V; Sousa, André M M; Jian, Xueqiu; Gottesman, Rebecca; Mosley, Thomas H; Fornage, Myriam; et al.
Abstract: We have carried out meta-analyses of genome-wide association studies (GWAS) ( n = 23 784) of the first two principal components (PCs) that group together cortical regions with shared variance in their surface area. PC1 (global) captured variations of most regions, whereas PC2 (visual) was specific to the primary and secondary visual cortices. We identified a total of 18 (PC1) and 17 (PC2) independent loci, which were replicated in another 25 746 individuals. The loci of the global PC1 included those associated previously with intracranial volume and/or general cognitive function, such as MAPT and IGF2BP1 . The loci of the visual PC2 included DAAM1, a key player in the planar-cell-polarity pathway. We then tested associations with occupational aptitudes and, as predicted, found that the global PC1 was associated with General Learning Ability, and the visual PC2 was associated with the Form Perception aptitude. These results suggest that interindividual variations in global and regional development of the human cerebral cortex (and its molecular architecture) cascade—albeit in a very limited manner—to behaviors as complex as the choice of one's occupation.